2020
DOI: 10.1186/s12887-020-1944-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibiotic and acyclovir usage before and after the implementation of an on-site FilmArray meningitis/encephalitis panel in an academic tertiary pediatric hospital: a retrospective observational study

Abstract: Background: Prompt initiation of empiric therapy is common practice in case of suspected meningitis or encephalitis. However, in children the most common pathogens are viruses that usually do not require and are not covered by the applied anti-infective treatment. Novel multiplex PCR (mPCR) panels provide rapid on-site diagnostic testing for a variety of pathogens. This study compared empiric antibiotic and acyclovir usage before and after the introduction of an on-site FilmArray Meningitis/Encephalitis Panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…One clear-cut benefit of FA-ME is the significant improvement in herpes simplex virus (HSV) turnaround time, which can lead to decreased acyclovir exposure. 15 , 16 Early diagnosis of aseptic meningitis through detection of enterovirus or parechovirus can allow providers to avoid antibiotics and possibly negate the need for hospital admissions. 17 Limited data have been published on the economic benefits and patient outcomes associated with the FA-ME, but the data we have report hospital cost savings and decreased length of stay.…”
Section: Meningitis/encephalitis Syndromic Panelmentioning
confidence: 99%
“…One clear-cut benefit of FA-ME is the significant improvement in herpes simplex virus (HSV) turnaround time, which can lead to decreased acyclovir exposure. 15 , 16 Early diagnosis of aseptic meningitis through detection of enterovirus or parechovirus can allow providers to avoid antibiotics and possibly negate the need for hospital admissions. 17 Limited data have been published on the economic benefits and patient outcomes associated with the FA-ME, but the data we have report hospital cost savings and decreased length of stay.…”
Section: Meningitis/encephalitis Syndromic Panelmentioning
confidence: 99%
“…Use of the FilmArray Respiratory Panel for detecting influenza A (H1 and H3), influenza B, respiratory syncytial virus, rhinovirus, enterovirus, human metapneumovirus, parainfluenza virus types 1 through 4, coronaviruses (OC43, 229E, HKU1, and NL63), and adenovirus was associated with reduced length of stay, improved influenza detection, and antiviral use, and appeared to be safe. 105 Hagen et al 108 suggested that introduction of a FilmArray meningitis/encephalitis panel into routine clinical procedures is associated with significantly reduced length and days of therapy for empiric antiinfective treatment in children with suspected meningoencephalitis (4.0 versus 3.0, P ¼ .04, and 8.0 versus 6.0, P ¼ .02, respectively). Patients with exacerbation of airway disease should undergo respiratory virus testing at the POC using a comprehensive syndromic multiplex panel rather than a molecular POCT for influenza alone, which would not detect the majority of viruses associated with early antibiotic discontinuation.…”
Section: Clinical Chemistrymentioning
confidence: 99%
“…More recently, several studies demonstrated cost savings and reductions in antibiotic days of therapy (DoT) with implementation of the MEP [ 17 , 18 , 19 , 20 , 21 ]. Nabower et al demonstrated decreased length of stay (LOS) and fewer acyclovir doses administered, while Weber et al demonstrated hospital cost savings in a military treatment facility [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Posnakoglou et al supplemented these findings, demonstrating decreased LOS, a reduction in antimicrobial use, and a decrease in total cost [ 19 ]. Similarly, Hagen et al noted a decreased duration of empiric therapy, with the largest effect documented in infants [ 20 ]. Messacar et al focused on herpes simplex virus in patients >60 days of age and observed a doubling of herpes simplex virus testing with a reduction in acyclovir duration of therapy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%